Against his self, against his time: modernist aesthetic, post-war London, and the failure of imagination in J. M. Coetzee's Youth. Issue 1 (2nd January 2019) - Bhattacharya, Sourit
ABSTRACT: J. M. Coetzee's Youth (2002), born in the heated times of the reconciliation of races in South Africa, has invited scholarship primarily on two areas: the problem of storytelling and the nature of place. Its predominant aspects, modernism, and post-war London have hardly been taken up for an analytical discussion on the issues of land, race, and storytelling. These aspects merit attention for three specific reasons: to understand the nature of exile for a white intellectual or artist from a peripheral colonial geography to a white metropolitan centre and the related notion of 'real' and 'configured' racial foreignness in post-war London; to comprehend the 'evental' in art and city-space as against the everyday and the contemporary influenced by 1920s European modernism; and to see the masculinist aspect in such project, especially in relation to the problem of love. The essay concludes with the argument that the author's repeated focus on the aspect of John's conscious dismissal of his essentially Romantic nature for this modernist quest is a suggestion that art, entirely dissevered from contemporary social and political reality, is bound to be futile and failed.